The impact of Hurricane Maria on individuals living with non-communicable disease in Puerto Rico: the experience of 10 communities - Elizabeth L. Andrade; Amalis Cordova; Courtney Riggle-van Schagen; Megan Jula; Carlos E. Rodriguez-Diaz; M. Ivonne Rivera; Carlos Santos-Burgoa (BMC, 2022)
Abstract Background Coinciding with the rising non-communicable disease (NCD) prevalence worldwide is the increasing frequency and severity of natural hazards. Protecting populations with NCDs against natural hazards is ever more pressing given their increased risk of morbidity and mortality in disaster contexts. This investigation examined Hurricane Maria's impacts across ten lower SES municipalities in Puerto Rico with varying community characteristics and hurricane impacts to understand experiences of supporting individuals with NCD management in the six-month period following the hurricane. Methods We conducted 40 qualitative interviews with mayors, first responders, faith leaders, community leaders, and municipal employees from 10 municipalities in Puerto Rico. Using QSR NVivo software, we deductively and inductively coded interview transcripts and undertook thematic analysis to characterize community-level hurricane impact and consequences for NCD management, and to identify convergent and divergent themes. Results Damages to infrastructure, including healthcare facilities and roadways, complicated the provision of timely health care for NCDs, patient transport, and pharmaceutical/medical supply chain continuity. Lengthy power outages at both healthcare facilities and private residences were barriers to healthcare service delivery, use of medical equipment, and storage of prescription medications with refrigeration, and led to a widespread mental health crisis. Cascading failures such as fuel shortages further compounded these challenges. The consequences of these impacts included the reported exacerbation of health conditions and loss of life among NCD patients. Conclusions Study findings identify contributors to morbidity and mortality among individuals with NCDs following Hurricane Maria. With the growing frequency of catastrophic disasters from natural hazards, the experiences of communities that endured these impacts offer important lessons regarding policies and practices to better support community disaster resilience and address the evolving preparedness needs of NCD patients.